Anisotropic generalization of Buchdahl bound for specific stellar models - Ranjan Sharma; Arpita Ghosh; Soumik Bhattacharya; Shyam Das (European Physical Journal C: Particles and Fields, 2021)
Abstract Anisotropy is one factor that appears to be significantly important in the studies of relativistic compact stars. In this paper, we make a generalization of the Buchdahl limit by incorporating an anisotropic effect for a selected class of exact solutions describing anisotropic stellar objects. In the isotropic case of a homogeneous distribution, we regain the Buchdahl limit $$2M/R \le 8/9$$ 2 M / R ≤ 8 / 9 . Our investigation shows a direct link between the maximum allowed compactness and pressure anisotropy vi-a-vis geometry of the associated 3-space.